Market economic systems - Frederic L. Pryor (Luxembourg Income Study (LIS), 2004)
The new comparative economics has focused on individual institutions, rather than the economic system as a whole. This essay argues that economic systems should be defined in terms of clusters of complementary or covarying institutions. A cluster analysis of OECD countries using data on forty different economic institutions shows that four economic systems characterize these nations. Further, these systems have no significant impact on economic growth or inflation, but they do have an important influence on the distribution of income. An analysis of systemic change suggests that with economic development, the differences between economic systems become greater while the differences among nations with the same economic system become less, at least up to 1990.
Keywords: 330; Systemvergleich; Institutionalismus; Clusteranalyse; OECD-Staaten